Karakterisasi Spesies Averrhoa yang Tumbuh di Kota Kediri Berdasarkan Pendekatan Palinologi - Dwi Wahyuni; Hari Untarto Swandono (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
Averrhoa is a member of the Oxalidaceae family and has four types, namely Averrhoa carambola, Averrhoa bilimbi, Averrhoa leucopetala, Averrhoa dolichocarpa.. Among the four types of averhoa, the most commonly found growing and planted in Kediri's yards were Averrhoa carambola and Averrhoa bilimbi. Cultivation of this plant is usually done by vegetative and generative with seeds. Pollen has long been used as an indicator in plant taxonomy, because in pollen there are many secret characters. This study aims to determine characterization Averrhoa species that grow in Kediri City based on a palinological approach. The result of this research is Averrhoa pollen that grows in Kediri City has almost the same characteristics, namely very small size, spheroidal Prolate shape, trizonocolpate aperture and isopolar polarity. The similarity is so great because the environmental conditions in which these two types of plants grow are the same. The difference in the character of pollen that grows in Kediri City lies in its ornamentation. In Averrhoa carambola ornate Perforate-Foveolate and Averrhoa bilimbi with reticulate character. This difference in ornament is due to the fact that these two types of plants have different species.